Flowering of Areca catechu in Bogor Botanic Gardens - Angga Yudaputra; Rizmoon N. Zulkarnaen; Irvan F. Wanda; Joko R. Witono (The East Java Biological Society, 2016)
Areca catechu is a species of palms that widely distributed in Indonesia. This palm has unique characteristics and important roles of a tropical forest ecosystem. Indonesian local tribes used seed of this palm for traditionaly medicinal purposes. Information regarding of flowering of A.catechu is valuabe to support a genetic improvement program. Currently, the flowering information about this palm is still lack, thereby study that related with flowering of A. catechu is important to be conducted. This study aimed to provide information about the flowering of A.catechu species. The observation was started with randomly selection of three individuals A. catechu from the Moluccas island. There were 3 main observations which done in this study, included the observation of flowering phases period, morphological changes of each phases, and the micro-climate factors. Flowering A. catechu was categorized into 4 phases, including initiation, bud towards anthesis, anthesis and young fruit to maturity. Each of flowering phases have a different time. The flowering phases were not directly influenced by micro-climate factors. Trigona laeviceps was the most dominant insect visitor and wind was an abiotic factors that influenced the flowering of A. catechu.